2000
DOI: 10.1016/s0006-3495(00)76287-4
|View full text |Cite
|
Sign up to set email alerts
|

M2 Pore Mutations Convert the Glycine Receptor Channel from Being Anion- to Cation-Selective

Abstract: Three mutations in the M2 transmembrane domains of the chloride-conducting alpha1 homomeric glycine receptor (P250Delta, A251E, and T265V), which normally mediate fast inhibitory neurotransmission, produced a cation-selective channel with P(Cl)/P(Na), = 0.27 (wild-type P(Cl)/P(Na) = 25), a permeability sequence P(Cs) > P(K) > P(Na) > P(Li), an impermeability to Ca(2+), and a reduced glycine sensitivity. Outside-out patch measurements indicated reversed and accentuated rectification with extremely low mean sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
110
2
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(129 citation statements)
references
References 39 publications
(62 reference statements)
16
110
2
1
Order By: Relevance
“…In addition, it is likely that the inner and outer vestibules of the channel play a role in concentrating the appropriately charged ionic species (28); since we did not modify these regions, the 5-HT 3A -STM receptor may inadvertently be designed to effectively concentrate ions of the wrong charge. Indeed, similar observations reported for the converse glycine receptor STM described by Keramidas et al (2) make this an attractive hypothesis. We also investigated if D-tubocurarine or granisetron, both of which are antagonists of the 5-HT 3 receptor, could activate 5HT 3A -STM, but both compounds were inactive in this respect.…”
Section: Gating and Desensitization Of The 5-ht 3a -Stm-ligand-supporting
confidence: 75%
See 2 more Smart Citations
“…In addition, it is likely that the inner and outer vestibules of the channel play a role in concentrating the appropriately charged ionic species (28); since we did not modify these regions, the 5-HT 3A -STM receptor may inadvertently be designed to effectively concentrate ions of the wrong charge. Indeed, similar observations reported for the converse glycine receptor STM described by Keramidas et al (2) make this an attractive hypothesis. We also investigated if D-tubocurarine or granisetron, both of which are antagonists of the 5-HT 3 receptor, could activate 5HT 3A -STM, but both compounds were inactive in this respect.…”
Section: Gating and Desensitization Of The 5-ht 3a -Stm-ligand-supporting
confidence: 75%
“…Although we have previously been able to use fluctuation noise analysis to study the unitary conductance of the WT and mutant 5-HT 3 receptors (19), preliminary studies on the 5-HT 3A -STM receptor failed to detect any resolvable channel noise (alternating current signal). 2 These findings may therefore reflect a reduced single channel conductance of the receptor, but further studies would be required to support this conclusion. It might, however, be anticipated that the conductance of the mutant receptor would be low, since we have mutated one of the rings of charged residues that Imoto et al (12) has shown affect conductance in the nACh receptor.…”
Section: Gating and Desensitization Of The 5-ht 3a -Stm-ligand-mentioning
confidence: 94%
See 1 more Smart Citation
“…The engineered cysteines are located in the M1-M2 loop (G-2ЈC) and on the cytoplasmic side of the M2 helix (S2ЈC), a region known to be important for permeability and ion selectivity (15)(16)(17)(18)(19)(20)(21)(22)(23). Because of the magnitude and persistence of inhibition in both oocyte and HEK-293T cell expression systems, we investigated in more detail the Cd 2ϩ inhibition of the S2ЈC receptor.…”
Section: Discussionmentioning
confidence: 99%
“…How such functional distinctions arise among channels with highly conserved features has been a long-standing question. Previous work has focused on some specific charged loci in one or a few pLGIC members to identify potential influences on charge selectivity (5)(6)(7)(8). However, as noted in a paper by Cymes and Grosman in PNAS (9), a detailed analysis of the literature reveals that a large number of discrepancies exist and that no consensus mechanism has yet been attained.…”
mentioning
confidence: 99%